Highly Thermal and Electrochemical Stable Dinitrile Disiloxane as Co-Solvent for Use in Lithium-Ion Batteries. Issue 3 (6th January 2015) - Pohl, Benjamin; Wiemhöfer, Hans-Dieter
Abstract : Two component mixtures of dinitrile functionalized disiloxanes and ethylene carbonate were investigated as new solvent composition for liquid electrolytes in lithium-ion half-cells. Their thermal and chemical stability offer an enhanced safety due to the substitution of the usually used volatile noncyclic carbonates of standard electrolyte compositions by 1, 3-Bis(3-cyanopropyl)tetramethyldisiloxane which was tested in a 1:1 mixture with ethylene carbonate (denoted as dinitrile/EC). A wide electrochemical window up to 5.4 V vs. Li/Li + on Pt electrode was obtained using LiClO4 as lithium salt. The dinitrile/EC electrolyte shows ionic conductivities reaching 1 mS·cm −1 and viscosities of 13 mPa·s at 30°C. Half-cell tests using graphite and LFP electrodes yielded high capacity retentions of 90% of the initial capacity after more than 500 cycles.